Numerical inversion of the abel integral equation using homotopy perturbation method - Kumar S.; Singh O.P. (My University, 2025)
Many problems in physics like reconstruction of the radially distributed emissivity from the line-ofsight projected intensity, the 3-D image reconstruction from cone-beam projections in computerized tomography, etc. lead naturally, in the case of radial symmetry, to the study of Abels type integral equation. The aim of this communication is to propose a new algorithm for the Abel inversion by using the homotopy perturbation method. © 2010 Verlag der Zeitschrift für Naturforschung, Tübingen.